Direct Visualization of Exciton Transport in Defective Few‐Layer WS2 by Ultrafast Microscopy. Issue 2 (27th November 2019) - Liu, Huan; Wang, Chong; Zuo, Zhengguang; Liu, Dameng; Luo, Jianbin
Abstract: As defects usually limit the exciton diffusion in 2D transition metal dichalcogenides (TMDCs), the interaction knowledge of defects and exciton transport is crucial for achieving efficient TMDC‐based devices. A direct visualization of defect‐modulated exciton transport is developed in few‐layer WS2 by ultrafast transient absorption microscopy. Atomic‐scale defects are introduced by argon plasma treatment and identified by aberration‐corrected scanning transmission electron microscopy. Neutral excitons can be captured by defects to form bound excitons in 7.75–17.88 ps, which provide a nonradiative relaxation channel, leading to decreased exciton lifetime and diffusion coefficient. The exciton diffusion length of defective sample has a drastic reduction from 349.44 to 107.40 nm. These spatially and temporally resolved measurements reveal the interaction mechanism between defects and exciton transport dynamics in 2D TMDCs, giving a guideline for designing high‐performance TMDC‐based devices. Abstract : Defect‐limited exciton transport in defective few‐layer WS2 is directly visualized by ultrafast microscopy. Neutral excitons can be captured by defects to form bound excitons in 7.75–17.88 ps, leading to decreased exciton lifetime and diffusion coefficient. Compared with the pristine sample, the exciton transport length of the defective sample is dramatically reduced from 349.44 to 107.40 nm.